A Review on Epoxy and Polyester Based Polymer Concrete and Exploration of Polyfurfuryl Alcohol as Polymer Concrete. (16th June 2016) - Kumar, Rakesh
Abstract : Petroleum based epoxy and polyester based thermoset resins can be used to produce high-quality polymer concrete. However, petroleum based resources are finite and this has necessitated the development of thermoset bioresins to be used as polymer concrete. Furfuryl alcohol (FA), a thermoset bioresin, is derived from lignocellulosic biomass and it can be polymerized into polyfurfuryl alcohol (PFA) in the presence of an acid catalyst. The highly exothermic polymerization reactions involving conversion of FA to PFA can be used to fabricate PFA based concrete with rock-like structure. The PFA based polymer concrete offers the broadest range of chemical resistance against acid and alkali over all other types of polymer concrete which are based upon different thermoset polymeric systems. In this review paper, we have discussed the formulations (incorporation of aggregates, fillers, and resin) and properties (especially compressive and flexural) of epoxy and polyester based polymer concrete. In another section, we have given the mechanical, thermal, and water resistance properties of PFA based biopolymer, biocomposites, nanocomposites, and polymer concrete. Lastly, we have tried to explore whether PFA can be used successfully as biopolymer concrete or not.